2007
DOI: 10.4049/jimmunol.179.5.3047
|View full text |Cite
|
Sign up to set email alerts
|

Virally Induced CD4+ T Cell Depletion Is Not Sufficient to Induce AIDS in a Natural Host

Abstract: Peripheral blood CD4+ T cell counts are a key measure for assessing disease progression and need for antiretroviral therapy in HIV-infected patients. More recently, studies have demonstrated a dramatic depletion of mucosal CD4+ T cells during acute infection that is maintained during chronic pathogenic HIV as well as SIV infection. A different clinical disease course is observed during the infection of natural hosts of SIV infection, such as sooty mangabeys (Cercocebus atys), which typically do not progress to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(160 citation statements)
references
References 53 publications
4
154
0
2
Order By: Relevance
“…Interestingly, an even more dramatic depletion of MALT CD4 ϩ T cells (i.e., to Ͻ0.5% of total T cells; Fig. 1D) was observed in two persistently asymptomatic SMs that were experimentally infected via SIV passage from a naturally infected SM and that developed systemic CD4 ϩ T cell depletion coincident with expanded SIV coreceptor tropism (33). In all, these results indicate that nonpathogenic SIV infection of SMs is associated with a significant depletion of MALT CD4 ϩ T cells that is, however, not followed by progression to AIDS.…”
Section: Cd4 ϩ T Cell Depletion In Malt Of Naturally Siv-infected Smsmentioning
confidence: 99%
“…Interestingly, an even more dramatic depletion of MALT CD4 ϩ T cells (i.e., to Ͻ0.5% of total T cells; Fig. 1D) was observed in two persistently asymptomatic SMs that were experimentally infected via SIV passage from a naturally infected SM and that developed systemic CD4 ϩ T cell depletion coincident with expanded SIV coreceptor tropism (33). In all, these results indicate that nonpathogenic SIV infection of SMs is associated with a significant depletion of MALT CD4 ϩ T cells that is, however, not followed by progression to AIDS.…”
Section: Cd4 ϩ T Cell Depletion In Malt Of Naturally Siv-infected Smsmentioning
confidence: 99%
“…Intriguingly, two naturally SIV-infected SMs have been discovered with levels of CD4 + T cells below 50 cells/mm 2 , i.e., a CD4 + T cell count that would place HIV-infected humans or SIV-infected RMs at high risk of opportunistic infections and death (19). Important insights into the pathogenesis of this unusual "CD4-low" phenotype of a minority of SIV-infected SMs were provided by a recent study that revealed that extreme (i.e., less than 0.2% of residual CD4 + T cells) and generalized (i.e., observed in blood, lymph nodes, and mucosal tissues) CD4 + T cell depletion can be observed in SIV-infected SMs in association with the emergence of SIV strains with an expanded coreceptor tropism (62). The ability to use CXC chemokine receptor 4 (CXCR4) as well as CCR5 as a coreceptor for virus entry is highly uncommon in SIV-infected SMs as well as other natural hosts (with only SIVagm.sab strains using CXCR4), as primary SIV isolates have previously been found to use mainly CCR5 as a coreceptor for host cell entry (63,64).…”
Section: Extreme Cd4 + T Cell Depletion In Sms Infected With Dual-tromentioning
confidence: 99%
“…These animals do not progress to AIDS. 27,28 Although immune activation during acute infection is present in these natural hosts, it resolves quickly, even though the virus continues to replicate at high levels. Dr. Silvestri and others have postulated that this rapid immunoregulatory response protects animals from the deleterious effects of chronic immune activation.…”
Section: Immune Activation In Viral Infectionmentioning
confidence: 99%